2020
DOI: 10.3846/jbem.2020.11959
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarity of Hybrid Entrepreneurs – Revisiting Lazear’s Theory of Entrepreneurship

Abstract: The aim of this study is to explore and elaborate the concept of hybrid entrepreneurship, i.e., a simultaneous mix of self-employment (entrepreneurship) and salary employment. Lazear’s theory of entrepreneurship is assessed in terms whether it can explain the phenomenon of being a hybrid entrepreneur. The hypothesis is that the probability of linking a salary job with one’s own business increases with the variety and level of education gained, the broadness of professional and management experience but also th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 59 publications
(77 reference statements)
2
14
1
4
Order By: Relevance
“…The multiple routes into tutoring demonstrate that we need to avoid framing entry into entrepreneurship in oppositional terms as push and pull factors co-exist in dynamic labour markets and intersect to shape the complex decision-making strategies of individuals moving into solo self-employment. Finally, the multitude of boundary crossings which saw teachers move into tutoring, student tutors planning a move into teaching and numerous people combining paid employment in schools (and elsewhere) with self-employed tutoring highlights the importance of hybridity (Bögenhold, 2019;Kurczewska et al, 2020). Entrepreneurship and paid employment do not simply stand in binary opposition to one another, and economic researchers must therefore do more to explore the hybrid nature of entrepreneurship, recognising its two-way relations between, and combination with, the shifting world of paid employment.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple routes into tutoring demonstrate that we need to avoid framing entry into entrepreneurship in oppositional terms as push and pull factors co-exist in dynamic labour markets and intersect to shape the complex decision-making strategies of individuals moving into solo self-employment. Finally, the multitude of boundary crossings which saw teachers move into tutoring, student tutors planning a move into teaching and numerous people combining paid employment in schools (and elsewhere) with self-employed tutoring highlights the importance of hybridity (Bögenhold, 2019;Kurczewska et al, 2020). Entrepreneurship and paid employment do not simply stand in binary opposition to one another, and economic researchers must therefore do more to explore the hybrid nature of entrepreneurship, recognising its two-way relations between, and combination with, the shifting world of paid employment.…”
Section: Discussionmentioning
confidence: 99%
“…As one establishes entrepreneurial competencies throughout the hybrid phase, their selfefficacy in their ability to successfully establish and maintain their venture is affected. The concept of self-efficacy is well developed in psychology literature and was successfully transferred to the entrepreneurship literature (Kurczewska et al, 2020). An individual's belief that (s)he is able to produce a positive outcome, or self-efficacy, has been studied as a determining factor of entrepreneurial intentions, opportunity, intuition and success (Markman et al, 2002;Barakat et al, 2014;Fietze and Boyd, 2017;Kurczewska et al, 2020).…”
Section: Self-efficacymentioning
confidence: 99%
“…Research has identified that a link exists between having high entrepreneurial self-efficacy and deciding to enter entrepreneurship (Zhao et al, 2005;Kurczewska et al, 2020). Barakat et al (2014, p. 457) define entrepreneurial self-efficacy as "an individual's own belief about his/ her skills and abilities linked to entrepreneurial activity".…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…As we are interested in what makes individuals successful in setting up and running a business, we look closer at one of the most recognised theories of career choice and entrepreneurship (Hsieh et al, 2017;Kurczewska et al, 2020) offered by Lazear (2005) and confirmed in many other empirical studies (for example, Tegtmeier et al, 2016;Astebro and Thompson, 2011;Backes-Gellner and Moog, 2013;Hartog et al, 2010;Stuetzer et al, 2013;Wagner, 2003, Wagner, 2006. His theory explains individual selection into entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%